Temozolomid and treatment of brain tumours - Słomian, Grzegorz; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2003)
Temozolomide, an oral cytostatic drug is imidazotetrazinon related to dacarbazine and procarbazine. This drug is rapidly absorbed after oral administration and achieves high concentration in the cerebrospinal liquid. Temozolomide is active in astrocytomas, malignant melanoma, the breast, ovarian, prostate, colorectal and non-small lung cancer, mesothelioma, malignant lymphomas and sarcomas. A group of 9 patients (3 women and 6 men) treated with Temozolomide due to brain tumours at the Cancer Centre in Gliwice was analysed. The age of patients ranged from 25 to 60 (mean age 42). Seven of them (77.7%) were treated due to astrocytoma relapses after surgery and radiotherapy and two (22.3%) due to progression of melanoma brain metastases after palliative irradiation. Temozolomide was administered 150–200 mg/m2 on five consecutive days every 28 days. Patients received 1 to 8 cycles of treatment. In the group of patients with primary brain tumours a complete regression was achieved in one case (14.2%), partial regression in two cases (28.4%) and disease progression during treatment in two cases (28.4%). The response rate was 3 (42.8%). Patients with melanoma brain metastases did not achieve the objective response. Temozolomide was generally well tolerated. The toxicity was moderate and acceptable. The grade 1 and 2 (WHO) neutropenia appeared in two cases (5.6%), grade 3 trombocytopenia in one case (2.8%) and grade 1 and 2 nausea and vomits in two cases. The time to progression ranged from 6 weeks to 30 months (mean 14.4) in patients with primary brain tumours and 3 weeks and 2 months, respectively, in 2 patients with melanoma brain metastases. Overall survival ranged from 7 weeks to 30 months (mean 15.1) in the patient group with primary brain tumours and 5 weeks and 3 months, respectively in 2 patients with melanoma brain metastases. One patient with primary brain tumour continues treatment. The discussion and obtained results (considering a small group) allow to conclude that oral Temozolomide chemotherapy is a safe and easy treatment modality for patients with recurrent gliomas and brain metastases of malignant melanoma giving moderate effect and probably should undergo further prospective clinical trials.